Progression of lung disease on computed tomography and pulmonary function tests in children and adults with cystic fibrosis. Issue 1 (21st October 2005) - de Jong, P A; Lindblad, A; Rubin, L; Hop, W C J; de Jongste, J C; Brink, M; Tiddens, H A W M
Abstract : Background: A study was undertaken to compare the ability of computed tomographic (CT) scores and pulmonary function tests to detect changes in lung disease in children and adults with cystic fibrosis (CF). Methods: CT scans and pulmonary function tests were retrospectively studied in a cohort of patients with CF aged 5–52 years for whom two or three CT scans at 3 year intervals were available, together with pulmonary function test results. All CT scans were scored by two observers. Pulmonary function results were expressed as percentage predicted and Z scores. Results: Of 119 patients studied, two CT scans were available in 92 patients and three in 24. CT (composite and component) scores and lung function both deteriorated significantly (p<0.02). Peripheral bronchiectasis worsened by 1.7% per year in children (p<0.0001) and by 1.5% per year in adults (p<0.0001). Bronchiectasis worsened in 68 of 92 patients while forced expiratory volume in 1 second (FEV1 ) worsened in 54 of 92 patients; bronchiectasis also deteriorated in 27 patients with stable or improving FEV1 . The CT score (and its components) and pulmonary function tests showed similar rates of deterioration in adults and children (p>0.09). Conclusion: The peripheral bronchiectasis CT score deteriorates faster and more frequently than lung function parameters in children and adults with CF, which indicates that pulmonary function tests and CT scans measure different aspects of CF lung disease. Our data support previous findings that the peripheral bronchiectasis CT score has an added value to pulmonary function tests in monitoring CF lung disease.